1988
DOI: 10.1159/000210778
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Inflammation

Abstract: The main elements of neurogenic inflammation in the skin – antidromic vasodilatation, axon reflex flare and neurogenic plasma extravasation – are briefly described. New evidence is presented for a contribution from small myelinated fibres, as well as unmyelinated fibres, to antidromic vasodilatation. The mechanisms underlying flare are discussed and it is argued that weak coupling between C-fibre terminals must be important in determining the extent of spread of vasodilatation. The extent to which neurogenic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 29 publications
1
37
1
3
Order By: Relevance
“…These results suggested that CGRP released from the peripheral nerve endings may stimulate the proangiogenic activities. Axon reflex is an event that was brought about by the passage of nerve impulses from sensory nerve endings to the effector organ along divisions of the nerve fibers without traversing a synapse (22). Axon reflex elicited by nociceptive stimulation may be closely related to the increased release of CGRP from nerve endings.…”
Section: Effects Of Continuous Infusion Of a Cgrp Antagonist On Tumormentioning
confidence: 99%
“…These results suggested that CGRP released from the peripheral nerve endings may stimulate the proangiogenic activities. Axon reflex is an event that was brought about by the passage of nerve impulses from sensory nerve endings to the effector organ along divisions of the nerve fibers without traversing a synapse (22). Axon reflex elicited by nociceptive stimulation may be closely related to the increased release of CGRP from nerve endings.…”
Section: Effects Of Continuous Infusion Of a Cgrp Antagonist On Tumormentioning
confidence: 99%
“…9 This increased vascular permeability, accompanied by release of vasoactive mediators from mast cells, results in an inflammatory response (neurogenic edema). 10 The increased vascular permeability also results in extravasation of additional algogenic (pain producing) substances, such as histamine and serotonin. Histamine can also be released from mast cells during degranulation, a process promoted by substance P, kinins, interleukin-1 and nerve growth factor.…”
Section: Transductionmentioning
confidence: 99%
“…Alternatively there may be some special feature in the anatomical organization of the microvasculature that is involved. It has also been suggested that spread of flare involves weak coupling between C fibre terminals (Lembeck, 1983;Lynn, 1988;Lynn & Cotsell, 1991). If the coupling involved organized synapses it might be directional and this could explain the asymmetry of the flare responses, however, at the moment, there is no evidence for such links between afferent terminals in skin.…”
Section: Discussionmentioning
confidence: 99%